Seasonality of influenza and other respiratory viruses - Neumann, Gabriele; Kawaoka, Yoshihiro (EMBO Molecular Medicine, 2022)
In virology, the term seasonality describes variations in virus prevalence at more or less regular intervals throughout the year. Specifically, it has long been recognized that outbreaks of human influenza viruses, respiratory syncytial virus (RSV), and human coronaviruses occur in temperate climates during the winter season, whereas low activity is detected during the summer months. Other human respiratory viruses, such as parainfluenza viruses, human metapneumoviruses, and rhinoviruses, show highest activity during the spring or fall season in temperate regions, depending on the virus and subtype. In tropical climates, influenza viruses circulate throughout the year and no distinct seasonal patterns are observed, although virus outbreaks tend to spike during the rainy season. Overall, seasonality is more pronounced with greater distance from the equator, and tends to be less pronounced in regions closer to the equator (Li et al , 2019). Graphical Abstract Respiratory viruses may follow different patterns of dissemination during pandemics and epidemics. Climate conditions have less effect on pandemic virus spread, which appears to depend more on human behavior. Once pandemic viruses become endemic, they may adopt seasonal patterns that are primarily driven by climate changes throughout the year.